Sosialisasi Pengelolaan Manajemen Persediaan pada UMKM - Bunfa, Liaw; Rakhman, Abdulah; Fuad, Muhammad (SANISKALA : Jurnal Pengabdian Masyarakat, 2023)
Abdimas aims to increase the active involvement of participants in dealing with common problems that often occur in Micro, Small and Medium Enterprises (MSMEs), with a focus on cases in the Garudayaksa Nusantara Cooperative, Jakarta. This activity carries a delivery method through lectures, questions and answers, and in-depth discussions on supply issues. Participants in this activity received direct assistance from the manager and management of Koperasi Garudayaksa Nusantara, Jakarta, who shared their experiences and insights in managing inventory. The main objective of this activity was to provide a comprehensive education on the importance of implementing a proper inventory management system in a company. Emphasis was placed on the dangers that may occur if inventory is not managed properly. Excessively large inventories can result in high storage costs and a higher risk of damaged goods. Therefore, through lectures, Q&A, and case discussions, participants were directed to understand the best practices in controlling inventory so that companies can be more efficient and effective in resource management. This activity is a concrete effort to empower MSMEs in dealing with the challenges faced in their inventory management. In addition, through direct interaction with the management of Koperasi Garudayaksa Nusantara, the participants were also able to understand real examples of best practices in managing inventory. As a result, it is expected that MSMEs will be better prepared and competent in optimising their inventory for sustainable growth.